Modeling of complex state financial support for small and medium-sized enterprises - Kristina Alekseyevna Zakharova; Danil Anatolyevich Muravyev; Egine Araratovna Karagulian (Economies, 2024)
This article describes a new approach to determining the optimal amount of state financial support provided to business entities. It is shown that there are three available methods to support economic agents. The most cost-effective option is subsidizing business entities to expand their current assets. It has been revealed that there are not just optimal amounts of government financial support but also optimal not-to-exceed amounts that make it possible to identify the boundaries of the so-called highly productive state of the economy. In this case, when the economy is highly productive, the prices of goods (services) fall, workers spend their savings, and the volume of production increases. This ultimately leads to an increase in the well-being of the population. The differential equations are the basis for the model, which is similar to the model of a simple two-sector single-product economy. The Monte Carlo method is used to determine the optimal not-to-exceed amount for government financial support. The identification of such intervals allows us to determine the amount of state financial support that will lead to a highly productive state and will not contribute to an unreasonable expansion of the budget expenditure. This study's results can be utilized by government authorities for the development of a comprehensive system of state financial support for entrepreneurship. Business entities can use the results of this research concerning the calculation of the optimal not-to-exceed amount of financial support.
Keywords: 330; mathematical modeling; not-to-exceed amount; state financial support; subsidies; two-sector economy